Fire performance of Pinus taeda wood treated with zinc borate before and after leaching - Camargo, Alvaro; Ibáñez, Claudia Marcela (Maderas. Ciencia y Tecnología, 2024)
Owing to its physico-mechanical properties, wood is widely used in housing for both outdoor structures and indoors in floors, ceilings and others. However, its vulnerability to fire makes protection necessary for occupant safety and damage prevention. In this study, the fire performance of Pinus taeda (loblolly pine) wood from northeastern Uruguay treated with zinc borate synthetized in our laboratory is tested. The effect of leaching on zinc borate fire retardant properties was also evaluated. The following parameters associated with the thermal degradation process of wood were analyzed: flame spread, carbonized area, carbonization index and mass loss. The wood was radially and tangentially exposed to the flame in a Vandersall tunnel under controlled conditions for three exposure times: 30, 60, and 80 seconds. The micromorphology of the surfaces exposed to the flame at each exposure time was analyzed with a scanning electron microscope in order to evaluate fiber damage, zinc borate distribution within the wood, and the effects of leaching on fire performance. A clear improvement in the fire resistance of the zinc borate -treated wood could be verified for all exposure times; leaching did not affect its fire retardant properties despite the harsh conditions of the test, making the product potentially suitable for outdoor use.